The prevalence of small airways disease and association with handgrip strength in young Hispanic farmworkers - Yutong Dong; Pam Cromer; Debbie Layman; Michelle Altvater; Yanbin Dong; Haidong Zhu (BMC Pulmonary Medicine)
Abstract Background Small airways disease (SAD) is a key risk in developing obstructive lung diseases (OLD). Handgrip strength (HGS) is found to be associated with pulmonary function in populations with lung conditions. Hispanics remain the main workforce in farming industry, but their prevalence of lung conditions remain understudied. Likewise, HGS also remains understudied in Hispanic and farmworker populations. Our study investigated the prevalence of SAD and OLD as well as their associations with HGS among Hispanic farmworkers. Methods A cross-sectional study analyzed 113 Hispanic farmworkers (54% female) who were screened using pulmonary function tests during annual health fairs in rural Southeastern US from 2013 to 2017. Smoking status was self-reported. SAD was defined as forced expiratory flow at 25–75% predicted of vital capacity (FEF25-75%predicted) ≤ 60% per literature and OLD defined as forced expiratory volume in 1 s/ forced vital capacity (FEV1/FVC) ratio < 70% per Global Initiative for Chronic Obstructive Lung Disease criteria. Seated isometric absolute (the sum of both hands) and relative (absolute handgrip strength divided by body mass index) handgrip strengths were collected. Results 26.5% of subjects had SAD and 15.9% had OLD. 50% of subjects with SAD had OLD while 83% of subjects with OLD had SAD. 13% of overall population smoked. Lower absolute and relative HGS groups had higher prevalence of SAD and OLD. Multivariate linear regression showed that lower absolute and relative HGS were associated with worsened small airway function. Age and FEF25-75%predicted were associated with FEV1/FVC. Smoking, body mass index, blood pressures, hemoglobin A1C and lipids were not predictors in either model. Conclusions This is one of the first studies reporting prevalence of pulmonary function in Hispanic farmworkers. Although this population was relatively young and healthy, there was high prevalence of SAD and OLD, which was higher than the overall prevalence in Hispanic population. There were more females subjects with SAD. Most of the subjects with OLD had SAD but not vice versa. Lower HGS levels were associated with worsened pulmonary function, and HGS was a significant predictor of FEF25-75%predicted, a potential marker for small airway physiology.